(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2019)
Stenocereus griseus is a cactus that has been effective as a coagulant in the clarification of waters with low turbidity (20 UNT-100 UNT) and very high (200 UNT-300 UNT). The objective of this investigation was to evaluate the effectiveness of the crude mucilage extracted from S. griseus in the clarification of waters with high turbidity (100 UNT-200 UNT). The tests were performed on a laboratory scale. Synthetic waters adjusted to turbidity between 100 NTU and 200 NTU were prepared, which were treated with different doses of S. griseus and characterized physicochemically (turbidity, pH, color and alkalinity). The simulation of the clarification process showed turbidity removals that oscillated between 83.77% and 91.78% before filtering and between 94.68% and 97.94% afterwards. After the filtration stage, the pH was in the range of 6.23-6.98, the alkalinity presented values lower than 40 mg CaCO3 / L and the color varied from 13.33 UC Pt / Co to 26.67 UC Pt / Co. These results demonstrate the effectiveness of the coagulant extracted from S. griseus for the removal of turbidity and color in waters with high turbidity, being able to use as a primary coagulant.